The smart negative pressure (SNaP) wound care system: A case series from Singapore - Wee, Ian J. Y. (Int Wound J, 2019)
The Smart Negative Pressure (SNaP) wound care system is a novel device that is single‐patient use, ultra‐portable, and light weight and does not rely on battery or need recharging. A systematic search was performed on major databases to identify relevant articles including case reports, retrospective case series, and randomised controlled trials. Ten studies were identified, showing that the SNaP wound care system is an effective tool in treating small‐sized wounds and may serve as an alternative to current electrically powered modalities. Furthermore, the system's small size and convenience leads to greater patient satisfaction and improves quality of life. Finally, we report our initial positive experiences with two cases in our institution. Although the evidence thus far has been encouraging, and patient satisfaction is higher than other wound care systems, further evidence is required to determine its superiority over current systems in terms of wound‐healing outcomes.